2003
DOI: 10.1002/mana.200310122
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Besov spaces and h‐sets

Abstract: In this paper we define Besov-type spaces with generalised smoothness on a rather vast class of (isotropic) irregular sets of fractal type in the Euclidean space (h-sets). As a special case we shall obtain the definition of Besov spaces with the usual scalar-index of regularity. To deal with this problem we rely on the one hand on the measure-geometric theory we have developed for h-sets and, on the other, we rely on some known results for Besov spaces with generalised smoothness in R n and on some advanced te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 20 publications
1
42
0
Order By: Relevance
“…Let us recall the definition and some properties of h-sets in R n studied in [3]. As we have already said, we will rely on what is known about this kind of sets in R n to extend this theory to more general spaces.…”
Section: Besov Spaces Of Generalised Smoothness On H-setsmentioning
confidence: 99%
See 4 more Smart Citations
“…Let us recall the definition and some properties of h-sets in R n studied in [3]. As we have already said, we will rely on what is known about this kind of sets in R n to extend this theory to more general spaces.…”
Section: Besov Spaces Of Generalised Smoothness On H-setsmentioning
confidence: 99%
“…The above definition was given in [3,Chapter 3], where Bricchi showed that the definition makes sense and that, if we apply it to σ = (0), we get…”
Section: Remark 43 If the Function H Is Given Bymentioning
confidence: 99%
See 3 more Smart Citations